Vegetation Analysis in the Freshwater Swamp Ecosystem of Tangkas Lake, Muaro Jambi - Rahmilija, Femei; Nursanti, Nursanti; Adriadi, Ade; Sari, Novita; Anggraini, Riana (Jurnal Biologi Tropis, 2025)
Tangkas Lake, a freshwater swamp in Muaro Jambi and Batanghari, is dominated by Homalium sp., but its overall plant diversity remains undocumented. This study inventories plant species as a baseline for conservation. Plant sampling was conducted using transect and plot methods in two locations, Pulau Tepus and Rawa Liontin, over two months. A total of 37 species from 21 families were recorded, with higher diversity in Pulau Tepus (31 species, dominated by Myrtaceae, Elaeocarpaceae, and Euphorbiaceae) compared to Rawa Liontin (6 species, dominated by Homalium sp.). Species diversity indices were moderate in Pulau Tepus but lower in Rawa Liontin. Species richness was highest in Pulau Tepus for tree (4.6) and seedling (4.5) stages, while pole-stage richness was 3.7. Rawa Liontin had low species richness across all stages, with low evenness in both sites. Environmental factors varied, with Pulau Tepus experiencing wider temperature fluctuations (23–30°C), lower light intensity, and sandy loam soils, while Rawa Liontin had a narrower temperature range (25.5–27.3°C), higher light intensity, and similar soil texture. Soil pH ranged from 4.29 to 6.21. These findings highlight the need for conservation, particularly in Rawa Liontin. Further research is needed to support habitat restoration and long-term monitoring.